Model-Based Computational Analysis on the Effectiveness of Enhanced Recovery after Surgery in the Operating Room with Nursing - Li, Wenji; Huang, Shu; Xie, Yong; Chen, Guanyu; Yuan, Jun; Yang, Yun (Frontiers in Surgery, 2022)
Objective In order to better understand the relative surgerical process, this work used a model-based computational analysis on effectiveness of enhanced recovery after surgery (ERAS) in operating room with nursing. Methods A total of 360 surgical patients from June 2020 to March 2021 in the first affiliated hospital, Sun Yat-sen university were randomly divided into observation group and control group, with 180 cases in each group. Routine nursing was used in the control group while ERAS was implemented in the observation group from four aspects which include preoperative visit, intraoperative cooperation, postoperative return visit and psychological intervention respectively. Results The postoperative complications, average hospital stay, nursing satisfaction and postoperative quality of life in the observation group were significantly better than those in the control group (all p<0.05). Conclusion The application of ERAS for surgical patients can enhance team awareness, optimize cooperation process, reduce surgical complications and improve nursing quality and improve prognosis, which is worthy to be popularized in the operating room.